1989
DOI: 10.1088/0022-3727/22/11/022
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric study of the influence of thermal cycling on the martensitic transformation of Cu-Zn-Al alloys

Abstract: A calorimetric study of the effect of thermal cycling on the martensitic transformation of Cu-Zn-Al shape-memory alloys is presented. The transformation kinetics become smoother when the number of cycles increases, and start progressively at higher temperatures and finish at lower ones. The use of a high-sensitivity calorimeter has, for the first time, enabled the study of the evolution of the elastic and frictional energies involved in the thermoelastic balance. It is shown that dislocations created in therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The thermal cycling of Cu-Zn-Al single crystals containing different distributions of y-precipitates was studied from a macroscopic point of view by means of calorimetry [ I l l . The evolution of transformation characteristics was found to be different for the three distributions of precipitates studied, depending on the size, coherency and density of precipitates, and also different from that obtained in precipitate-free specimens [4].…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…The thermal cycling of Cu-Zn-Al single crystals containing different distributions of y-precipitates was studied from a macroscopic point of view by means of calorimetry [ I l l . The evolution of transformation characteristics was found to be different for the three distributions of precipitates studied, depending on the size, coherency and density of precipitates, and also different from that obtained in precipitate-free specimens [4].…”
Section: Introductionmentioning
confidence: 61%
“…The results shown in table 1 present the same behaviour than those of [ I l l : high stability of the hysteresis loop during cycling of sample 2, as was also observed in sample 1, and a shift of the transformation temperatures (mainly the direct transformation ones) to higher temperatures for sample 3. The decrease in Q and AS can be related to the presence of retained martensite as it occurs in precipitate-free samples [4].…”
Section: Calorimetric Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successive thermal cycling through a martensitic transformation is known to produce an evolution of transformation temperature [5-71 which has been related to dislocation arrays formed during thermal cycling [8]. However, the presence of precipitates (y phase) inside the parent f3 phase also affects the transformation behaviour [9-111 and the size, coherency and density of precipitates have been found to be important variables [12]. Recent work has shown that by using a complex heat treatment schedule involving step quenching and flash heating a distribution of precipitates of a mean size of approximately 30nm can be produced and the martensitic transformation temperatures of an alloy resulting from such a heat treatment do not change over 200 thermal cycles [13,14].…”
Section: Introductionmentioning
confidence: 99%